Pengembangan Flashcard Digital untuk Meningkatkan Penguasaan dan Pemahaman Kosakata Siswa Kelas II Sekolah Dasar - Shafira Dini, Faza; Zainuddin, Almuntaqo (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This study aims to develop digital flashcard learning media to enhance vocabulary understanding and mastery among second-grade students at SD Negeri Kertonatan 01. The development model used is ADDIE, which consists of five stages: analysis, design, development, implementation, and evaluation. The media was designed using Canva and converted to the Heyzine.com website with added vocabulary audio. Validation was carried out by media and material experts to assess the feasibility of the media, followed by trials involving teachers and seven students. The research findings indicate that the digital flashcards are feasible and reasonably effective for learning. Media expert validation resulted in a score of 74.6%, while material expert validation reached 78%, both categorized as